Incidence of Occult Uterine Pathology in Women Undergoing Hysterectomy With Pelvic Organ Prolapse Repair. Issue 5 (September 2016) - Ackenbom, Mary F.; Giugale, Lauren E.; Wang, Yanting; Shepherd, Jonathan P.
Abstract : Objectives: The objectives of this study are to determine the incidence of and associated risk factors for occult uterine pathology in patients undergoing hysterectomy with pelvic organ prolapse (POP) repair. Methods: Medical records were reviewed from all cases of hysterectomy with POP surgery at a tertiary medical center from January 2007 through July 2014. Exclusion criteria included known endometrial hyperplasia or malignancy. A power calculation determined that 1000 subjects would demonstrate a lower rate of leiomyosarcoma in a urogynecology population compared to the rate of 1:352 reported by the Food and Drug Administration. Results: There were 1196 cases identified with a mean age of 62.3 ± 11.3 years and body mass index of 27.8 ± 5.7. Most patients were white (95.5%) and postmenopausal (81.6%). Malignancy was present in 3 (0.3%) specimens. Seven (0.6%) specimens had endometrial hyperplasia. This overall abnormal pathology incidence of 0.8%, with 95% confidence interval of 0% to 1.4% is significantly lower than published rates of 2.6% ( P < 0.001). There were no specimens with sarcoma (rate of 0%; 95% confidence interval, 0%–0.2%). There were no associations between demographic or clinical variables with the presence of hyperplasia and/or malignancy. Conclusions: The incidence of uterine hyperplasia/malignancy and sarcoma in women undergoing hysterectomy with POP were both significantly lower than previously published values in other populations. The use of power morcellation in urogynecologic populations should be revisited as the incidence of occult pathology is lower than the general population, and a condition-specific risk profile should be considered in the informed consent process. Abstract : Uterine pathology in women undergoing hysterectomy with pelvic organ prolapse repair was lower than other populations, supporting reconsideration of power morcellator use in these patients.